Resting-State Pallidal-Cortical Oscillatory Couplings in Patients With Predominant Phasic and Tonic Dystonia - Yokochi, Fusako; Kato, Kenji; Iwamuro, Hirokazu; Kamiyama, Tsutomu; Kimura, Katsuo; Yugeta, Akihiro; Okiyama, Ryoichi; Taniguchi, Makoto; Kumada, Satoko; Ushiba, Junichi (Frontiers in Neurology, 2018)
Pallidal deep brain stimulation (DBS) improves the symptoms of dystonia. The improvement processes of phasic symptoms and tonic symptoms differ. Phasic symptoms improve rapidly after starting DBS treatment, but tonic symptoms improve gradually. This difference implies distinct neuronal mechanisms for phasic and tonic symptoms in the underlying cortico-basal ganglia (BG) neuronal network. Phasic symptoms are related to the pallido-thalamo-cortical pathway. But, the pathway related to tonic symptoms, especially truncal dystonia, has been unknown and assumed to be different from that for phasic symptoms. The purpose of this study is to investigate the different characteristics　related to the two symptoms by recording　local field potentials (LFPs) in the internal pallidum (GPi), external　pallidum (GPe) and EEGs recorded from the motor cortex (MCx). The symptoms of dystonia are complicated and the pathophysiology of dystonia is not clear. It is possible that understanding of the neuronal circuits in the background of dystonia symptoms become a clue of pathogenesis of dystonia. LFPs and EEGs were recorded in 19 dystonic patients to analyze the differences between the two types of symptoms. Patients were divided into two groups, 10 with predominant phasic symptoms (phasic patients), and 9 with predominant tonic symptoms (tonic patients). To investigate the distinct features of oscillations and functional couplings across the GPi, GPe, and MCx by clinical phenotype, power and coherence were calculated over the delta (2-4 Hz), theta (5-7 Hz), alpha (8-13 Hz), and beta (14-35 Hz) frequencies. In phasic patients, the alpha spectral peaks emerged in the GPi oscillatory activities, and alpha GPi coherence with the GPe and MCx was higher than in tonic patients. On the other hand, delta GPi oscillatory activities were prominent, and delta GPi–GPe coherence was significantly higher in tonic than in phasic patients. However, there was no significant delta coherence between the GPi/GPe and MCx in tonic patients. These results suggest that different pathophysiological cortico-pallidal oscillations are related to tonic and phasic symptoms.